An analysis of the implementation of the Indonesian culture in English class - Dwi Wahyuningtyas (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2021)
As a multicultural country, Indonesia has many cultures that must be taught to its people, especially to university students through some university subjects. However, not all students understand well about their own culture, which becomes one of the main concerns of the lecturer and the students themselves. Therefore, the curriculum is then designed to enable students to learn about the culture aside from their courses. One of the lessons that also allows students to understand their own culture is English. In this study, the researcher chooses English II, the English lesson given to second-semester students. Students are encouraged to learn the language during the English class while also learning the Indonesian culture to know more about it and raise their awareness to preserve it. Some topics included Indonesian Literature, Wayang and Other Indonesian Art Performances, and some other issues that may be closely related to the Indonesian culture substances. The lesson problems were presented in some ways, including presentation, discussion, storytelling, and role-play. Therefore, this study aims to analyze how Indonesian culture is embedded in students’ lesson materials. This study uses observation and documentation as to its data collection. Meanwhile, the study revealed some classroom activities and assignments that indicate the implementation of the Indonesian culture in English II Classes. Keywords: Analysis, Implementation, Indonesian, Culture, English Class